Joint planning of distribution network and electric vehicle charging station considering extreme weather events. Issue 1 (1st May 2022) - Liao, Jie; Wang, Rui; Xia, Shiwei; Ren, Lijun; Wang, Tong
Abstract: In order to deal with the increasing demand for electric vehicle charging and the increasingly frequent extreme weather events, this paper proposes a distribution network-electric vehicle charging station planning method considering extreme ice and snow weather conditions. Firstly, the influence mechanism of extreme ice and snow weather on distribution network line failure rate and traffic network section capacity is studied. Then the Distflow optimal power flow model is established and relaxed into a second-order cone model. Secondly, based on Wardrop user equilibrium, the distribution of mixed traffic flow between electric vehicles and non-electric vehicles is studied and the model is linearized. Finally, considering the multiple faults of the distribution network in extreme ice and snow weather, the distribution network electricity and the electric vehicle charging station are coordinated to support the key loads of the distribution network. In this paper, a planning model is established with the objective function of minimizing the annualized investment cost and the weighted operating cost under normal and extreme weather conditions, and the proposed model as a mixed-integer second-order cone problem is solved by the Yalmip toolbox. The results show that the proposed joint planning model can improve the utilization rate of equipment investment and the daily operation economy on the premise of ensuring key load supply in extreme events.